Analysis Customer Satisfaction and its Implications for Customer Loyalty and Purchase Intention for Cinepolis Cinemas Tickets - Girsang, Rosita Manawari; Lie, Darwin; Fedianty Augustinah; Sudirman, Acai (Universitas Pendidikan Ganesha, 2024)
This study aims to analyze the effect of E-service quality, price perception, brand image, and perceived value on customer satisfaction, as well as its implications for customer loyalty and ticket purchase intention of Cinepolis Cinemas. This study used a quantitative approach involving 120 respondents as a sample. The sampling method uses a non-probability sampling approach using a purposive sampling formula. The results showed that price perception, brand image, and perceived value positively and significantly affect customer satisfaction. In addition, customer satisfaction also has a positive and significant effect on customer loyalty and purchase intent. Nevertheless, the quality of E-service has a positive but not significant effect on customer satisfaction. Therefore, it is concluded that to maintain customer satisfaction with Cinepolis Cinemas tickets, companies need to improve the quality aspects of E-service, especially in terms of completeness of online payment features and data security for online service users. This research provides valuable insights for companies in improving customer satisfaction, customer loyalty, and purchase intent through improving price perception, brand image, perceived value, and E-service quality. The implications of these findings could help companies develop more effective marketing strategies and improve the overall customer experience.